دور التكوين في إحداث التغيير التنظيمي لتحسين الأداء المؤسسي "دراسة ميدانية بمؤسسة المصبرات الغذائية - Cabوحدة بوعاتي محمود" - سلاطنية, إبتسام; غياط, شريف (جامعة الوادي - University of Eloued, 2022)
This study aimed to shed light on the role entrusted with the process of human resource formation in bringing about the necessary organizational change in economic institutions, in order to improve performance and keep abreast of developments and changes taking place at the level of the international economy, as well as to maintain the competitive position, as it relied on a questionnaire distributed to the employees of Amor Ben Amor Corporation Food Canister (CAB) as a pioneer in the food industry. To achieve the desired goals and test hypotheses, the study relied on primary and secondary data, using the SPSSV25.0 program and other statistical tools. The study concluded with a set of results, the most prominent of which is the adoption and effecting of organizational change in the economic institution, which is one of the most important influencing factors that contribute to improving and upgrading performance, as this process requires a broad and accurate understanding of the nature of the change to be brought about in various fields, which is usually related to many. Among the various elements, on top of which is the human resource, is his possession of the intellectual and technical skills that contribute greatly to planning, implementing and following up the organizational change processes
The role of Training in Bringing about Organizational Change to Improve Enterprise Performance "An Empirical Study at the CAB Food Caster Enterprise -Bouati Mahmoud Unit"
مقال
Keywords: المورد البشري؛ التكوين؛ التغيير التنظيمي؛ تحسين الأداء; Human resource; Training; organizational change; performance improvement